Eksplorasi Ambiguitas Makna dalam Lirik Lagu Membasuh: Sebuah Pendekatan Semantik dengan Makna Kontekstual - Jelita Maulida Nurhamidah; Bintang Putri Pamungkas; Fikri Hakim (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study delves into the ambiguity of meaning in the lyrics of “Membasuh” using a semantic approach through a contextual method. Finding the lyrics' hidden meanings and how listeners' context shapes their interpretations are the main goals of this study. By applying contextual semantic analysis, this study explores the words and phrases in the lyrics to uncover how these meanings are formed and interpreted in various contexts. The findings indicate that the ambiguity in the lyrics of “Membasuh” not only enriches the listening experience but also allows listeners to discover meanings that are personal and contextually relevant. This research provides significant contributions to understanding the complexity of meaning in song lyrics and offers new insights into the study of contextual semantics.